Diameter of the Superior Ophthalmic Vein in Relation to Intracranial Pressure - Lirng, Jiing-Feng; Fuh, Jong-Ling; Wu, Zin-An; Lu, Shiang-Ru; Wang, Shuu-Jiun (American Journal of Neuroradiology, 2003)
BACKGROUND AND PURPOSE: Bilateral engorged superior ophthalmic veins (SOV) have been reported in patients with diffuse brain swelling. We investigated the relationship between the diameter of the SOV on brain MR images and the intracranial pressure (ICP).METHODS: We reviewed the medical records of neurologic inpatients who had undergone both MR imaging of the brain and lumbar puncture. MR imaging had to have been performed before lumbar puncture, and the two studies had to have occurred within 2 days. The diameters of the SOV were measured on coronal contrast-enhanced fat-saturated T1-weighted MR images. For this, the image nearest the rear of the globe of the eye was chosen.RESULTS: Sixty-nine patients (32 male, 37 female; mean age, 46 years ± 19) were included. The average diameters of the SOV and the ICP were positively correlated (r = 0.58, P < .001), if an SOV diameter of <1 mm was treated as 0.5 mm for calculations. In patients with increased ICP (CSF pressure >200 mm H2O), SOV diameters were larger than those of patients with a normal CSF pressure (3.0 vs 1.6 mm, P < .001). Frequencies of increased ICP were 3% among patients with an average SOV diameter of 0.5–1 mm, 15% for 1.5–2 mm, and 58% for 2.5–5 mm (P < .001).CONCLUSION: This study showed that the SOV diameter, determined on the basis on MR imaging, was positively correlated with ICP. Dilatation of the SOV should alert physicians to the possibility of increased ICP.